A case of cardiac herniation after right pneumonectomy. (July 2022) - Inoue, Manabu; Yotsukura, Masaya; Yoshida, Yukihiro; Nakagawa, Kazuo; Watanabe, Shun-ichi
A cardiac herniation is a rare but life-threatening complication after pneumonectomy. In most cases, it manifests suddenly as severe hypotension and cardiac arrest within 24 h of pneumonectomy. Here, we report a case of sudden-onset cardiac herniation after right pneumonectomy during which the pericardium was incised. The diagnosis was made immediately based on chest X-ray and electrocardiogram findings, and the heart was repositioned by repeat thoracotomy as an urgent life-saving measure. Surgeons should be aware of this potential surgical complication as well as its clinical manifestations, given that delayed diagnosis would directly lead to a fatal outcome.